Multifunctional biosensors based on peptide-polyelectrolyte conjugates - Kogikoski, S.; Sousa, C. P.; Liberato, M. S.; Andrade-Filho, T.; Prieto, T.; Ferreira, F. F.; Rocha, A. R. [UNESP]; Guha, S.; Alves, W. A. (Royal Society of Chemistry (RSC), 2016)
A novel enzymatic platform for the sensing of H2O2 and glucose that uses l,l-diphenylalanine micro/nanostructures (FF-MNSs) as an enzyme support is shown. This platform is obtained by the self-assembly of poly(allylamine hydrochloride) (PAH), FF-MNSs, and microperoxidase-11 (MP11) anchored onto the peptide matrix, in two different crystal structures of FF-MNSs: hexagonal (P61) and orthorhombic (P22121). The electroactive area of the electrodes increases in the presence of FF-MNSs. We also demonstrate via theoretical calculations that the valence band energy of the orthorhombic structure allows it to be doped, similarly to p-type semiconductors, where PAH acts as a doping agent for the orthorhombic peptide structure, decreasing the band-gap by around 1 eV, which results in a smaller charge transfer resistance. These results are consistent with electrochemical impedance spectroscopy measurements, which further elucidate the role of the band structure of the orthorhombic FF-MNSs in the conductivity and electron transfer rates of the hybrid material. An effective communication between the electrode and the active site of a glucose oxidase enzyme through MP11-protein complexes occurs, paving the way for FF-MNSs in the orthorhombic phase for the future development of bioelectronics sensing devices.